2003
DOI: 10.1128/ec.2.3.465-473.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expressed during Sexual and Asexual Sporulation in Phytophthora infestans Is a Member of the Puf Family of Translational Regulators

Abstract: A gene from Phytophthora infestans that was previously identified as being induced during the development of sexual spores was also found to be active during asexual sporulation. The gene, M90, was expressed as a 3.1-kb primary transcript containing two introns and was predicted to encode a member of the Puf family of translational regulators. The protein showed up to 51% amino acid identity to other Puf proteins within its 353-amino-acid RNA-binding domain. Little similarity extended beyond this region, as no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
29
1
Order By: Relevance
“…That M96 is expressed relatively late during mating was indicated by comparisons with mating-induced gene M90 (Cvitanich and Judelson 2003). Based on hybridizations against the same blots, M96 expression peaked after M90 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That M96 is expressed relatively late during mating was indicated by comparisons with mating-induced gene M90 (Cvitanich and Judelson 2003). Based on hybridizations against the same blots, M96 expression peaked after M90 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mating, carbon or nitrogen-starved, and nonmating cultures were as described (Judelson and Roberts 2002;Cvitanich and Judelson 2003). Tissue low in oospores from the homothallics (strain 6.11 and P. phaseoli) was obtained by growing hyphae submerged in clarified rye broth.…”
Section: Methodsmentioning
confidence: 99%
“…Previous RNA blot analyses from our laboratory indicated that traditional standards, such as actin and EF1, varied relative to rRNA in sporangia versus hyphae and thus would be inappropriate for normalization (10). Levels of EF1 were lower in sporangia than in hyphae, for example (Fig.…”
Section: Identification Of Genes Up-regulated In Asexual Sporangiamentioning
confidence: 99%
“…Stable transformants were obtained using a protoplast method and stained histochemically for ␤-glucuronidase (GUS) activity (24). This involved derivatives of pOGUS (14) into which wild-type or mutagenized portions of the PinifC1, PinifC3, and M82 promoters were inserted into the ApaI and ClaI sites upstream of GUS. pOGUS also contains an npt gene for G418 selection.…”
Section: Methodsmentioning
confidence: 99%